Doctor Strange. - Caramagna, Joe; Benjamin, Paul, 1970-; DeMatteis, J. M. (Marvel Worldwide, Inc., 2016)
Doctor Strange seeks help from Spider-Man, Bruce Banner, and Captain America when he comes up against Nightmare and Dread Dormammu.